2007
DOI: 10.1038/sj.jes.7500626
|View full text |Cite
|
Sign up to set email alerts
|

Further interpretation of the acute effect of nitrogen dioxide observed in Canadian time-series studies

Abstract: In this paper, the pooled NO 2 association with nonaccidental mortality is examined across 10 cities in Canada in single-and two-pollutant time-series models. The results reaffirm that NO 2 has the strongest association with mortality, particularly in the warm season. Although attributing such effects to NO 2 cannot be ruled out, it is plausible that NO 2 is acting as an indicator for some other exposure affecting the population. This could include PM 2.5 , as has been suggested from some personal exposure dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(94 citation statements)
references
References 33 publications
0
94
0
Order By: Relevance
“…This three-day lag was based on previous analyses which showed that the effects of air pollution did not persist past lag 2 days and the response functions were consistent with linearity (Brook et al 2007;Goldberg 2003;Goldberg 2006;Goldberg et al 2011). …”
Section: Methodsmentioning
confidence: 99%
“…This three-day lag was based on previous analyses which showed that the effects of air pollution did not persist past lag 2 days and the response functions were consistent with linearity (Brook et al 2007;Goldberg 2003;Goldberg 2006;Goldberg et al 2011). …”
Section: Methodsmentioning
confidence: 99%
“…The investigators noted that in Canadian cities, the major source of nitric oxide (NO) (80-90%) was exhaust from motor vehicles or other forms of transportation, suggesting that ambient concentrations of NO 2 might be serving as a surrogate of primary traffic-related pollutants. An updated analysis of the multicity Canadian study further examining the association of NO 2 and mortality is presented by Brook et al (2007) in this special issue. The findings suggest that NO 2 may be a better indicator of motor vehicle fine particles than PM 2.5 , thereby offering one explanation as to why some epidemiologic studies have found a stronger association between mortality and NO 2 than with PM 2.5 .…”
Section: Surrogate Measures Of Pollutant Mixturesmentioning
confidence: 99%
“…Strong associations exist between NO 2 and nonaccidental mortality in daily time series studies [Steib et al, 2003;Burnett et al, 2004;Samoli et al, 2006]. NO 2 concentrations are also highly correlated with other pollutants either emitted by the same sources or formed through complex reactions in the atmosphere [e.g., Brook et al, 2007]. Complete spatial coverage of ground-level NO 2 measurements are needed for exposure assessment.…”
Section: Introductionmentioning
confidence: 99%